Mapping of the Left‐Sided Phrenic Nerve Course in Patients Undergoing Left Atrial Catheter Ablations. Issue 9 (16th May 2014) - HUEMER, MARTIN; WUTZLER, ALEXANDER; PARWANI, ABDUL S.; ATTANASIO, PHILIPP; HAVERKAMP, WILHELM; BOLDT, LEIF‐HENDRIK
<x xml:space="preserve">Abstract</x> Background Catheter ablation of atrial fibrillation has been associated with left‐sided phrenic nerve palsy. Knowledge of the individual left phrenic nerve course therefore is essential to prevent nerve injury. The aim of this study was to test the feasibility of an intraprocedural pace mapping and reconstruction of the left phrenic nerve course and to characterize which anatomical areas are affected. Methods In patients undergoing left atrial catheter ablation, a three‐dimensional map of the left atrial anatomical structures was created. The left‐sided phrenic nerve course was determined by high‐output pace mapping and reconstructed in the map. Results In this study, 40 patients with atrial fibrillation or atrial tachycardias were included. Left phrenic nerve capture was observed in 23 (57.5%) patients. Phrenic nerve was captured in 22 (55%) patients inside the left atrial appendage, in 22 (55%) in distal parts, in 21 (53%) in medial parts, and in two (5%) in ostial parts of the appendage. In three (7.5%) patients, capture was found in the distal coronary sinus and in one (2.5%) patient in the left atrium near the left atrial appendage ostium. Ablation target was changed due to direct spatial relationship to the phrenic nerve in three (7.5%) patients. No phrenic nerve palsy was observed. Conclusions Left‐sided phrenic nerve capture was found inside and around the left atrial appendage in the majority of patients and additionally in the distal coronary sinus. Phrenic nerve mapping and reconstruction can easily be performed and should be considered prior catheter ablations in potential affected areas.